2019
DOI: 10.1002/jor.24546
|View full text |Cite
|
Sign up to set email alerts
|

Translational relevance of the goat as a preclinical model of the human labrum and chondrolabral junction—histological study

Abstract: The purpose of this study was to evaluate the histologic features of the caprine labrum, with emphasis on the chondrolabral junction, with the goal of informing the feasibility of the goat as an animal model. The left hip joint of six adolescent Spanish goats (Capra pyrenaica) was harvested and subjected to anatomical and histological assessments. Human acetabular and femoral head samples, collected during total hip arthroplasty, served as comparison samples. The caprine labrum was found to consist of mostly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This extension-recovery property allows the labrum to maintain its elasticity without undergoing permanent deformation. 48 Relatedly, cadaveric studies have revealed that disrupting the CLJ compromises the labrum's sealing capacity, elevating the risk for progression to osteoarthritis. 7,14,16,45 Despite these critical functions, a histologic study using an ovine model has suggested the CLJ possesses limited regenerative potential, with only partial healing via fibrovascular scarring observed 12 weeks after arthroscopic labral repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extension-recovery property allows the labrum to maintain its elasticity without undergoing permanent deformation. 48 Relatedly, cadaveric studies have revealed that disrupting the CLJ compromises the labrum's sealing capacity, elevating the risk for progression to osteoarthritis. 7,14,16,45 Despite these critical functions, a histologic study using an ovine model has suggested the CLJ possesses limited regenerative potential, with only partial healing via fibrovascular scarring observed 12 weeks after arthroscopic labral repair.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence elucidating the biomechanical and physiologic properties of the CLJ continues to increase, the relationship between CLJ breakdown and clinical outcomes after hip arthroscopy for labral pathologies and/or FAI has yet to be explored in available long-term analyses. 7 , 42 , 45 , 48 Thus, the purpose of this study was to (1) report minimum 8-year survivorship and PROMs after hip arthroscopy for symptomatic labral tears secondary to FAI and (2) characterize associations between outcomes and patient demographic characteristics (age, body mass index [BMI], sex), pathological parameters (Tönnis angle, alpha angle, type of FAI, CLJ breakdown), and procedures performed (labral management, FAI treatment, microfracture). We hypothesized that CLJ breakdown, older age, osteoarthritis (Tönnis grade >1 or Outerbridge grade >2), and joint space narrowing would predict conversion to THA.…”
mentioning
confidence: 99%
“…2,25 Additionally, since a local capsular autograft employs tissue that may have a preserved blood supply, there is a theoretical advantage of superior healing when compared with remote autograft techniques that require metaplasia with ingrowth of blood supply after reconstruction. 32 Moreover, remote autograft and allograft techniques require the debridement and removal of residual labrum before graft placement, risking damage to the chondrolabral junction and leaving the labrum susceptible to a possible ''out-ofround'' repair, which occurs when the contact between the articular surface of the labrum and corresponding femoral head is not restored once the joint is fully reduced. This alters the biomechanics of the hip and may predispose patients to accelerated osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…This alters the biomechanics of the hip and may predispose patients to accelerated osteoarthritis. 32,36,39 Ultimately, the lack of uniform outcome measurements and differences between surgeon experience, surgical technique, and patient indications for surgery limits direct comparison; thus, surgeons should take a patient-centered approach by taking patient characteristics into consideration as well as surgeon experience.…”
Section: Discussionmentioning
confidence: 99%
“…The aspiration and sub-culture of bone marrow stem cells was approved by our institutional animal care and use committee (IACUC). bMSCs were obtained from heparinized bone marrow from the iliac crests of an adult Spanish goat when it was sacrificed for other purposes [28,29] and identified as stem cells, as previously reported in our former publications [30]. As the cells from various goats behaved in comparable fashion, in the current study, in order to remove any interindividual variability (viz., age), cells from only one goat were employed.…”
Section: Mesenchymal Stem Cell Culture and Viability Of The Cells In Gelatin-hydroxyphenyl Propionic Acid Matrixmentioning
confidence: 96%